The iron dragon's mother - Swanwick, Michael (Tor, 2019)
Caitlin of House Sans Merci is the young half-human pilot of a sentient mechanical dragon. Returning from her first soul-stealing raid, she discovers an unwanted hitchhiker. When Caitlin is framed for the murder of her brother, to save herself she must disappear into Industrialized Faerie, looking for the one person who can clear her. Unfortunately, the stakes are higher than she knows. Her deeds will change her world forever.